Working memory exertion after simultaneous interpreting in bilinguals - Garcia-Serrano, A (Cambridge University Press, 2026)
Simultaneous interpreting (SI), a challenging task enabled by bilingualism, is claimed to distinctly tax working memory (WM). However, causal designs are missing, limiting our understanding of the phenomenon. We recruited 50 Chinese-English bilinguals and assessed their WM performance (alongside inhibitory and fluency outcomes) before and after L1–L2 SI or a control task (text comprehension). WM scores (especially under high-demand, multimodal conditions) increased after text comprehension but not after SI, adjusting for age of L2 appropriation, years of L2 use, L2 proficiency and SI competence. Of note, WM was assessed immediately before and after SI, ruling out other cognitive influences. Conversely, no distinct patterns were observed on inhibitory or fluency tasks. Briefly, this activity seems to hinder practice-related WM gains - a finding that expands contemporary accounts of interpreting. © The Author(s), 2026. Published by Cambridge University Press.